2014
DOI: 10.1515/chem-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of PSSA-Polyaniline Composite with an Enhanced Processability in Thin Films

Abstract: This paper reports the synthesis and investigation of a polymer composite based on poly(4-styrenesulfonic acid) (PSSA) and polyaniline (PANI) directly obtained in an aqueous PSSA medium, with improved conductivity and solubility in polar solvents. The oxidative polymerization reaction of aniline takes place in-situ with PSSA as protonating agent. The synthesis was tested at three PSSA/PANI molar ratios, an intense green colored aqueous composite solution being obtained in each case. For comparison purposes, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It can be noticed that increasing amount of PAni in the composite increased the weight loss, i.e., the addition of PAni decrease the thermal stability. The second and third loss steps are found at 450 and 520 C. From Table 2, it can be observed that the amount of weight loss is reduced at these higher temperatures compared to the value obtained at 340 C. These findings are in accordance with the results reported before by Corneliu et al [25]. The last degradation stage can be assigned for the decomposition of base chains and substituent sulphonate groups in the polystyrene [26].…”
Section: Ft-ir and Xrd Spectrasupporting
confidence: 90%
“…It can be noticed that increasing amount of PAni in the composite increased the weight loss, i.e., the addition of PAni decrease the thermal stability. The second and third loss steps are found at 450 and 520 C. From Table 2, it can be observed that the amount of weight loss is reduced at these higher temperatures compared to the value obtained at 340 C. These findings are in accordance with the results reported before by Corneliu et al [25]. The last degradation stage can be assigned for the decomposition of base chains and substituent sulphonate groups in the polystyrene [26].…”
Section: Ft-ir and Xrd Spectrasupporting
confidence: 90%
“…Regarding to PAni doped with DBS À , 750 mL of acetone (99.5%, Synth) was added to the polymerization solution to precipitate the polymer particles, followed by filtration and washing with plenty of water and dried in oven at 60 C for 24 h [48,49]. The particles of PAni doped with PSS À were separated by leaving the polymerization solution in an oven for 24 h at 60 C to evaporate the solvent [50]. The samples of PAni doped with the different anions were referred as PAni/Cl, PAni/PTS, PAni/DBS and PAni/PSS.…”
Section: Polyaniline Synthesismentioning
confidence: 99%
“…Figure 2e displays the absorption peaks for CH stretching of symmetric and asymmetric bonding [37] in PSS-H at ≈2856 and ≈2935 cm -1 as well as that for OH bond [37,38] in PSS-H and water at ≈3400 cm -1 . The FTIR spectra were normalized with respect to the peak at ≈2935 cm -1 so that the increment in OH peak intensity refers accrual of water at the interrogating location with time, which is pertinent to the thermo-diffusion of water in the sample.…”
Section: Resultsmentioning
confidence: 99%